Speciation of Silver Nanoparticles and Silver(I) by Reversed-Phase Liquid Chromatography Coupled to ICPMS - Soto-Alvaredo, Juan; Montes-Bayón, María; Bettmer, Jörg (Analytical chemistry (Washington), 2013)
The tremendous increase in the use of engineered nanoparticles in daily life has raised concerns about their impact on the environment and in biological systems. Among them, silver-containing material is of high industrial interest and of manifold use in consumer products, mainly because of their antimicrobial activity. Therefore, analytical methods are urgently needed for the reliable determination of Ag nanoparticles and their corresponding Ag(I) species. In this study, we present the development of coupling reversed-phase high-performance liquid chromatography (HPLC) to inductively coupled plasma-mass spectrometry (ICPMS) for the speciation of engineered Ag-containing nanoparticles and Ag(I) species. The method has been designed for the separation/detection of all investigated silver species in a single chromatographic run. For this purpose, the addition of thiosulfate to the mobile phase has been used to elute Ag(I) species from the column without degradation of the other species. The analytical figures of merit show repeatable results for the recoveries (>80%) of both, the Ag nanoparticles and Ag(I) species. The obtained detection limits are in the medium ng·L–1 range and therefore allow the trace analysis of the sought analytes in real samples. However, the matrix (e.g., fetal bovine serum) showed an impact on the retention behavior of the Ag nanoparticles, so that for size determinations the use of gold nanoparticles as internal size standard is suggested. Finally, the analysis of textile products exemplarily demonstrates the applicability to the analysis of real samples. Besides silver-containing nanoparticles, Ag(I) species can be identified as one of the major species in the extraction solution from sports socks. However, extraction conditions will be the subject of further investigations in the future in order to obtain reliable quantitative data.